Heaven and earth : making the psychic connection - Van Praagh, James (New York : Simon & Schuster Source, 2001)
In Heaven and Earth, world-renowned spiritual medium and bestselling author James Van Praagh reveals the techniques that anyone can use to contact "the other side." Combining his own experiences with the testimony of others who have been touched by their spirit guides, Van Praagh encourages us to embark on our own journey of discovery, teaching us to recognize and listen to our own inner voices alter our awareness to make contact with the spirits of the departed interpret our dreams as messages from beyond use our inherent psychic gifts to help and heal others Most of us go through life without developing the wonderful, natural, God-given abilities inherent in all of us. In Heaven and Earth, James Van Praagh gives us the tools to bring them to life.
Keywords: Psychic ability; Spiritualism